A importância da ciência Educação Física na preparação operacional de militares: premissas da Academia Militar dos Estados Unidos – West Point - Santos, Inaldo Pereira dos; Vieira, Luciano; Martins, Lilian (Revista de Educação Física / Journal of Physical Education, 2018)
Introdução: A Educação Física teve suas origens no treinamento físico militar. Nos dias atuais, a preparação física continua sendo uma das facetas mais importantes da operacionalidade militar. Objetivo: Descrever a importância do treinamento físico na preparação profissional do militar, por meio da observação dos objetivos e práticas educacionais do Departamento de Educação Física (DEF) da Academia de West Point (AWP) dos Estados Unidos da América. Conclusão: O DPE da AWP atinge o objetivo de preparar os cadetes para as situações que serão vividas em ambiente de guerra e faz isso com excelência, utilizando-se da Educação Física como ciência. The Importance of Physical Education Science for Operational Preparation of Military: Assumptions of the United States Military Academy – West Point Introduction: Physical Education had its origins in military physical training. Nowadays, physical preparation continues to be one of the most important facets of military operationality. Objective: To describe the importance of physical training for the professional preparation of the military, by observing the objectives and educational practices of the Department of Physical Education (DPE) of the West Point Academy (WPA) of the United States of America. Conclusion: WPA's DPE achieves the goal of preparing the cadets for situations that will be experienced in war environment and does so with excellence, using Physical Education sciences.